Cultural Governance through Local Traditions of the Kasepuhan Indigenous People of Paras Beswara - Fitriana Nurul Hidayati; Masruchin; Reva Rahma Maulida; Kilau Syamsiah; Alifia Davina Diwantari (PT FORMOSA CENDEKIA GLOBAL, 2023)
Kasepuhan adat is a cultural pattern owned by the community in a village, one of which is Paras Beswara which is unique with various local traditions as well as its customs. This study aims to determine the traditional ceremonial traditions in Paras Hamlet, Paras Beswara customary kasepuhan, and the habits of the Paras Hamlet people in their daily lives. The method used is descriptive-qualitative. Data analysis was carried out by collecting interview data, documentation, classification, and concluding sessions. The results of this study are the traditions and habits of the people of Paras Hamlet are able to fortify their lifestyle with their customary rules so that they are not mixed with cultures that have a negative impact. Most traditions play an important role in water management, one of which is the Ngunduh Patirtan tradition. The tradition of Napak Tilas Tirta is also a way to remember the struggle of water management actors from the source to channeling it to the community.